The Legal Liability of Marketplace Retailers for the Distribution of Counterfeit Goods in Indonesia - Abelita Daud; Dolot Alhasni Bakung; Mohammad Rivaldi Moha (Yayasan Cerdas Pedia Indonesia, 2026)
This study examines the legal liability of marketplace retailers concerning the distribution of counterfeit products across Indonesia. Utilizing a normative legal research methodology incorporating statutory, conceptual, and analytical approaches, this research thoroughly investigates retailer accountability within the expanding digital economy. The core findings demonstrate that retailers are strictly subject to civil liability through financial compensation, administrative liability via government sanctions, and contractual liability based on their agreements with consumers and digital platforms. The continuous circulation of counterfeit goods inherently violates consumer protection regulations and directly contravenes the fundamental principle of good faith, subsequently rendering associated sales agreements completely null and void under civil law. Furthermore, the current regulatory framework lacks comprehensive oversight mechanisms specifically targeting these digital retailers. Consequently, this study explicitly recommends strengthening legal regulations, enhancing mandatory product verification procedures by marketplace operators, and enforcing integrated preventive oversight between the state and platforms to effectively protect all vulnerable consumers.